High-dose 5-fluorouracil / folinic acid in combination with three-weekly mitomycin C in the treatment of advanced gastric cancer. A phase II study - Hofheinz, Ralf-Dieter; Hartung, G.; Samel, S.; Hochhaus, Andreas; Pichlmeier, U.; Post, Stefan; Hehlmann, Rüdiger; Queißer, Wolfgang (Onkologie, 2002)
Background: The 24-hour continuous infusion of 5-fluorouracil (5-FU) and folinic acid (FA) as part of several new multidrug chemotherapy regimens in advanced gastric cancer (AGC) has shown to be effective, with low toxicity. In a previous phase II study with 3-weekly bolus 5-FU, FA and mitomycin C (MMC) we found a low toxicity rate and response rates comparable to those of regimens such as ELF, FAM or FAMTX, and a promising median overall survival. In order to improve this MMC-dependent schedule we initiated a phase II study with high-dose 5-FU/FA and 3-weekly bolus MMC. Patients and Methods: From February, 1998 to September, 2000 we recruited 33 patients with AGC to receive weekly 24-hour 5-FU 2,600 mg/m2 preceded by 2-hour FA 500 mg/m2 for 6 weeks, followed by a 2-week rest period. Bolus MMC 10 mg/m2 was added in 3-weekly intervals. Treatment given on an outpatient basis, using portable pump systems, was repeated on day 57. Patients’ characteristics were: male/female ratio 20/13; median age 57 (27-75) years; median WHO status 1 (0-2). 18 patients had a primary AGC, and 15 showed a relapsed AGC. Median follow-up was 11.8 months (range of those surviving: 2.7-11.8 months). Results: 32 patients were evaluable for response - complete remission 9.1% (n = 3), partial remission 45.5% (n = 15), no change 27.3% (n = 9), progressive disease 15.1% (n = 5). Median overall survival time was 10.2 months [95% confidence interval (CI): 8.7-11.6], and median progression-free survival time was 7.6 months (95% CI: 4.4-10.9). The worst toxicities (%) observed were (CTC-NCI 1/2/3): leukopenia 45.5/18.2/6.1, thrombocytopenia 33.3/9.1/6.1, vomitus 24.2/9.1/0, diarrhea 36.4/6.1/3.0, stomatitis 18.2/9.1/0, hand-foot syndrome 12.1/0/0. Two patients developed hemolytic-uremic syndrome (HUS). Conclusions: High-dose 5-FU/FA/MMC is an effective and well-tolerated outpatient regimen for AGC (objective response rate 54.6%). It may serve as an alternative to cisplatin-containing regimens; however, it has to be considered that possibly HUS may occur.
Gesehen am 16.05.2022